CHARACTERIZATION OF SUBSURFACE LITHOLOGICAL UNITS AND AQUIFEROUS FORMATIONS USING INTEGRATED VLF AND VES TECHNIQUES IN OWO, ONDO STATE - Nosayaba Avenbuan; , Olalekan Ayodeji Omolegan; Diemeta Ikperikpe (Academy Journal of Science and Engineering)
This study applies integrated Very Low Frequency (VLF) electromagnetic profiling and Vertical Electrical Sounding (VES) to delineate groundwater potential zones in Owo, Ondo State, Nigeria. Utilizing the Schlumberger array configuration, subsurface resistivity variations revealed lithological units and aquiferous formations. VES results indicate an overburden depth of 24 metres – 27 metres with resistivity values between 43 Ωm and 50 Ωm, suggesting moderate hydrogeologic significance for groundwater development. The VLF pseudo section identifies conductive zones associated with groundwater-bearing structures, with isoline conductivity values ranging from 0.02 S/m in fractured zones to 0.26 S/m in fresh basement rock. The survey highlights a thick overburden (0–25 metres), underlain by a weathered basement (25 metres – 50 metres), a wet basement at 50 metres, and a thin fractured basement (80 metres – 90 metres). This research aims to optimise drilling site selection and enhance sustainable groundwater resource management in erosion-prone terrains. Aligned with Sustainable Development Goal (SDG) 6.2, which targets universal access to safe water, sanitation, and hygiene, the study underscores the critical role of geophysical methods in advancing water security, resilience, and equitable resource distribution in regions vulnerable to water scarcity.